PENGARUH ENDORSER, HARGA DAN KUALIATAS PRODUK TERHADAP PERILAKU PERALIHAN MEREK (BRAND SWITCHING) BEDAK PADAT MAYBELLINE DI KOTA PADANG - Reni Anggraeni; Susi Evanita; Rani Sofya (Universitas Negeri Padang, 2018)
The purpose of this study is to determine the effect of endorser, price and quality of products toward Brand Switching Maybelline Solid Powder in Padang. The type of research is descriptive and qualitative research. The sampling technique used is Purposive sampling. The type of data used is primary and secondary data. The data analysis technique used is multiple regression by using t test and F test. The result of the research shows that there is a positive and insignificant influence between endorser variables on brand switching behavior of Maybelline solid powder in Padang. Then for price variable has no effect on brand switching, but there is significant influence between product quality variable to brand switching of Maybelline solid powder in Padang. Keywords : endorser, price, product quality, brand switching